PENGARUH KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN DAN PENERAPAN SISTEM E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS KANTOR PELAYANAN PAJAK PRATAMA PONDOK GEDE) - Hj. Dewi Rejeki, SE., Ak., M.Ak. M.Si., CA.; Indah Permadani (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
The objective of this research is to find out the effect of Taxpayer Awereness, Tax Sanctions, and aplication of e-Filing system for individual Taxpayer compliance in KPP Pratama Pondok Gede. The research method is descriptive and quantitative research methods. The type of data is primary data.The results of this research had effect of taxpayer awareness, tax sanctions and aplication of e-Filing system for individual taxpayer compliance in KPP Pratama Pondok Gede. The conclusion of this research shows that taxpayer awereness has a partial effect on the compliance of individual taxpayer, tax sanctions don't have a partial effect on the compliance of individual tax payer, aplication of e-filing system has a partial effect on the compliance of individual tax payer, taxpayer awareness, tax sactions, and application of e-filing system has simultaneously affects on the compliance of individual taxpayer. From that conclusions, i suggest Direktorat Jenderal Pajak of The Republic of Indonesia, especially Kantor Pelayanan Pajak Pratama Pondok Gede, in order to increase educate and counseling to improve taxpayer compliance.